Integration of a Return-to-Work Module in Cognitive Behavioral Therapy in Patients With Major Depressive Disorder and Long-Term Sick Leave—A Feasibility Study - Winter, Lotta; Geldmacher, Julia; Plücker-Boss, Katharina; Kahl, Kai G. (Frontiers in Psychiatry, 2020)
Objective: Major depressive disorder (MDD) has a negative impact on individuals ability to work, and is often associated with long phases of sick-leave. Consequently, interventions facilitating return to work in patients with MDD gained increased attention during last decades. We here report results of a feasibility study where a “return-to-work” (RTW) module published by Lagerveld and colleagues in the Netherlands was integrated in cognitive behavioral therapy in depressed patients with long-term sick-leaves in Germany. Our study aimed to answer the following questions: Is RTW accepted by patients and therapists? Do RTW interventions lead to return-to-work? Do depressive symptoms improve? Methods: Twenty patients with major depressive disorder (15 female, mean age 45±9y) were included. Patients received cognitive-behavioral therapy with an integrated, standardized return-to-work module (W-CBT). Psychometric measurements included Beck Depression Inventory (BDI-2) and work ability index (WAI). Further, time until return-to-work was measured, and acceptability of W-CBT was assessed using visual analogue scales and open questions. Results: Mean sick-leave days in depressed patients were 127±97, and 75% of patients were sick-leave for more than 6 weeks. After treatment, 11/20 patients had returned to their former occupation (55%), 5/20 were in occupational re-deployment or started a new job (25%), and 3/20 patients were still on sick-leave (2/20; 10%) or received a pension (1/20; 5%). One patient dropped out. BDI-2 sum score improved from 23±8 to 8±5 (p<0.001), and WAI improved from 28±6 to 39±7 (p<0.001). Acceptability of W-CBT in patients and therapists was high. Conclusion: We here demonstrate feasibility and acceptability of an RTW module integrated in standard cognitive behavioral therapy. W-CBT leads to improvement of work ability, paralleled by improvement of depressive symptoms. Despite the limitations of this uncontrolled study, the results propose that W-CBT may be feasible in the treatment of depressed patients with long sick-leaves and justify a controlled trial evaluating the efficacy of W-CBT.